Strategic Management in the Dynamic Business Environment: A Comprehensive Analysis - Jayadi, Usman; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2025)
Strategic management plays a crucial role in ensuring the sustainability and growth of organizations in a competitive and ever-changing business environment. The process of formulating, implementing, and evaluating strategies is vital for organizations to achieve long-term objectives while adapting to market demands and external pressures. This article explores the concept of strategic management, emphasizing the strategic planning process and the various tools and frameworks used to analyze internal and external factors that influence organizational performance. It further examines the role of leadership and decision-making in driving successful strategies, considering both traditional models and contemporary approaches such as agile strategy and innovation-driven growth. Using a case study approach, the article illustrates how different organizations implement strategic management practices to overcome challenges and capitalize on opportunities. The research concludes by discussing the future of strategic management in an increasingly complex global business landscape, stressing the importance of flexibility, sustainability, and alignment with technological advancements. By analyzing relevant theories and practical insights, this article contributes to the existing body of knowledge on strategic management and provides recommendations for managers to improve their strategic decision-making processes.